Perbandingan Metode SOM/Kohonen dengan ART 2 pada Data Mining Perusahaan Retail - Ariana, Anak Agung Gede Bagus; Darma Putra, I Ketut Gede; Linawati, Linawati (Jurnal Teknologi Elektro; Vol 16 No 2 (2017): (May - Agustus) Majalah Ilmiah Teknologi Elektro, 2017)
Abstract — This study investigates the performance of artificial neural network method on clustering method. Using UD. Fenny’s customer profile in year 2009 data set with the Recency, Frequency and Monetary model data. Clustering methods were compared in this study is between the Self Organizing Map and Adaptive Resonance Theory 2. The performance evaluation method validation is measured by the index cluster validation. Validation index clusters are used, among others, Davies-Bouldin index, index and index Dunn Silhouette. The test results show the method Self Organizing Map is better to process the data clustering.
Keywords: Data Mining; Jaringan Saraf Tiruan; Self Organizing Map; Adaptive Resonance Theory 2